Sol-gel-based highly sensitive Pd/n-ZnO thin film/n-Si schottky ultraviolet photodiodes - Yadav A.B.; Pandey A.; Somvanshi D.; Jit S. (My University, 2025)
High-performance ultraviolet (UV) Schottky photodiodes obtained by growing Pd Schottky contacts on the sol-gel-derived n-ZnO thin films deposited on n-Si substrates have been reported in this paper. The current-voltage (I-V) measurements of the as-fabricated Schottky photodiodes show an excellent room temperature contrast ratio (i.e., the ratio of the current under UV illumination to the dark current) of ~5.332 × 103 and responsivity (i.e., the parameter characterizing the sensitivity of the device to the UV light) of ~8.39 A/W at -5 V reverse bias voltage, respectively; when the device is illuminated by an UV source of ~650 μW output power at ~365 nm. The measured room temperature contrast ratio and responsivity are believed to be the highest among the reported values in the literature for ZnO thin film-based Schottky photodiodes using sol-gel method. © 2015 IEEE. Personal use is permitted.